Error patterns in parameterized digital assessment in mathematics - BRĂNOAEA, Gabriela Cristina; BRAICOV, Andrei; BRAGARU, Tudor (Acta et Commentationes, Sciences of Education, 2026)
This paper examines how parameterized items contribute to the identification and stabilization of error patterns in lower secondary mathematics digital assessment. The study is embedded in a pedagogical experiment conducted on the Moodle platform within the implementation of an Intelligent Support System. Based on data collected from grades 5–8, the research analyzes performance evolution across attempts, internal consistency of test batteries, and score distribution. The findings suggest that numerical variability does not alter the cognitive structure of items, but enables a more refined analysis of recurrent difficulties and supports data-informed formative interventions